2018
DOI: 10.4067/s0718-221x2018005041901
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopy of the surface of thermally-modified teak juvenile wood

Abstract: During the thermal modification of the wood there is a decreasing gradient of temperature from the surface to its interior, therefore, the most severe chemical modifications occur on the surface. These chemical modifications directly affect the quality and durability of adhesives and coating. Therefore, this study investigated the chemical modification of the surface of thermally-modified teak juvenile wood. Heartwood and sapwood samples were treated at 180 and 200ºC. Chemical analyses were performed by Fourie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…The increase in lignin content after the thermal modification process was also observed by Kamdem et al (2002), Tjeerdsma and Militz (2005), Esteves et al (2008), González-Peña et al (2009), Brosse et al (2010), Ding et al (2011), Esteves et al (2011), Moura et al (2012) and Sikora et al (2018). According to Esteves et al (2013) and Cademartori et al (2015), the increase in the percentage of lignin is due to the degradation of carbohydrates (hemicelluloses) and the formation of carbonyl groups in lignin (Li et al, 2002;Lopes et al, 2018).…”
Section: Discussionsupporting
confidence: 55%
“…The increase in lignin content after the thermal modification process was also observed by Kamdem et al (2002), Tjeerdsma and Militz (2005), Esteves et al (2008), González-Peña et al (2009), Brosse et al (2010), Ding et al (2011), Esteves et al (2011), Moura et al (2012) and Sikora et al (2018). According to Esteves et al (2013) and Cademartori et al (2015), the increase in the percentage of lignin is due to the degradation of carbohydrates (hemicelluloses) and the formation of carbonyl groups in lignin (Li et al, 2002;Lopes et al, 2018).…”
Section: Discussionsupporting
confidence: 55%
“…For NaBH4-SG1.2, the additional peaks observed at 2582, 1194, 1077, and 994 cm -1 were assigned to the C-O stretching modes associated with NaOCH3 [21][22][23][24][25][26][27][28][29]. Such vibrations were not observed at higher molar ratio of NaOCH3 and B2H6 and this confirmed that above a ratio of 1.2, NaOCH3 was fully reacted.…”
Section: Composition Of the As-synthesized Materialsmentioning
confidence: 54%
“…The highest wavenumber in bioplastics with the addition of 40% glycerol concentration was 3313.80 cm −1 . This hydroxyl group indicated the presence of polymer compounds (Lopes et al, 2018). The di erent concentrations of glycerol plasticizer lead to the di erent transmittance spectrum due to the addition of glycerol which resulted from hydrogen bonds formation (Jannah, 2017).…”
Section: The E Ect Of Type and Concentration Of Plasticizer Onmentioning
confidence: 99%